Influence of solid acid catalyst on DME production directly from synthesis gas over the admixed catalyst of Cu/ZnO/Al2O3 and various SAPO catalysts - Yoo, Kye Sang; Kim, Ji-Hyun; Park, Min-Jo; Kim, Sun-Jin; Joo, Oh-Shim; Jung, Kwang-Deog (ELSEVIER SCIENCE BV, 2007)
This study focused on the effect of solid acid catalyst on the catalytic performance in direct DME synthesis. The various SAPO catalysts were prepared to perform methanol dehydration and direct DME synthesis. In methanol dehydration, SAPO-34 and -18 with strong acid sites and showed high initial activity, but deactivated rapidly. This is mainly attributed to the formation of coking materials inside the pore of the catalysts. In contrast, SAPO-5 and -11 with low initial activity showed relatively high catalytic stability. The high stability of both catalysts is due to their mild acid sites and desirable pore architecture. For direct DME synthesis from synthesis gas, various admixed catalyst were prepared with a commercial Cu/ZnO/Al2O3 and the SAPO catalysts. The initial activity of all the catalysts was comparable in the direct DME synthesis with the admixed catalysts, even though those catalysts showed quite different catalytic activity in methanol dehydration. Indeed, admixed SAPO-5 and -11 showed better catalytic stability than the other admixed catalysts. The results indicate that catalytic stability of solid acid is essential factor to determine catalytic performance in the reaction. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: DIMETHYL ETHER; METHANOL SYNTHESIS; CONVERSION; PERFORMANCE; ZEOLITES; HYDROCARBONS; SYNGAS